Report of Two COVID-19 ARDS (CARDS) Cases Who Survived without Intubation and Mechanical Ventilation - Arto Yuwono Soeroto; Yovita Hartantri; Jipi E Perkusi; Ferdy Ferdian; Undang Rehimat; Hendarsyah Suryadinata (Acta Medica Indonesiana)
The most severe clinical feature of COVID-19 is Acute Respiratory Distress Syndrome (ARDS) which requires intubation and mechanical ventilation and it occurs in approximately 2.3% of cases. About 94% of of these cases end in death. This case series report two confirmed COVID-19 patients who had met criteria of intubation and mechanical ventilation, but not performed to them. Both patients experienced clinical improvement and recovery. Probably this is due to differences of COVID-19 ARDS (CARDS) with typical or classic ARDS.  CARDS is divided into two phenotypes of type L (Low Elastance) and type H (High Elastance). These different phenotypic also distinguish subsequent pathophysiology and clinical management. These phenotype can be differentiate by chest CT scan. This case series emphasizes the importance of understanding this phenotype so that clinicians can provide more appropriate treatment management and also availability of CT scans in health facilities that manage COVID -19.